A knowledge identification framework for component based dependency analysis process - Ratneshwer; Tripathi A.K. (My University, 2025)
Knowledge engineering applied to the Component Based Software Engineering (CBSE) field is an important research area that focuses on identification, specification and validation of knowledge and experiences acquired during various phases of component based software development cycle. This work presents a systematic approach to knowledge identification in dependency analysis process in context of CBSE, which results a well defined approach for representing dependency analysis information in form of knowledge artifacts. The identified knowledge artifacts and knowledge relationships may help in design optimization, fault management, configuration management and testing processes ©2013 SERSC.